Conversational Modeling for Constraint Satisfaction - Freuder, Eugene C. (Proceedings of the AAAI Conference on Artificial Intelligence, 2024)
Many problems, from Sudoku to factory scheduling, can be regarded as constraint satisfaction problems. A key component of real world problem solving is a conversation between a constraint programming expert and a problem domain expert to specify the problem to be solved. This presentation argues that the time is ripe for progress in automating the constraint programmer side of this conversation and suggests promising avenues for this pursuit.